Development of a dynamic user interface for an electronic device descriptions interpreter for intelligent sensors - Pushkarskiy R. V. (Мехатроника и робототехника, 2024)
To solve the problem of supporting intelligent sensors manufactured in the Russian Federation by foreign software, Aspect LLC has developed a HART-compatible Colibri field bus. Within the framework of the Colibri project, the Colibri software is being developed to work with intelligent sensors and their electronic descriptions